АСОЦІАЦІЇ МІЖ ІНФІЛЬТРАЦІЄЮ ПУХЛИНОАСОЦІЙОВАНИХ МАКРОФАГІВ І ЦИТОКІНОВИМИ ТА EСМСИГНАТУРАМИ В МІКРООТОЧЕННІ РАКУ МОЛОЧНОЇ ЗАЛОЗИ - Pavlova, A.; Mushii, O.; Zadvornyi, T.; Bazas, V.; Karacharova, I.; Lukianova, N. (PH Akademperiodyka, 2026)
Background: Tumor-associated macrophages (TAMs) are among the main regulators of the immune microenvironment of breast cancer (BC). Still, their relationships with cytokine signals and the state of the extracellular matrix (ECM) remain poorly characterized. The study aimed to evaluate associations of the degree of infiltration with CD68+ and CD163+ macrophages (Mj) with the status of pro-inflammatory and immunosuppressive cytokines, as well as with the expression of the key ECM proteins in BC tissue. Materials and Methods. Postoperative material from 67 patients with stage I—II BC was studied. TAMs infiltration and the expression of SPP1, COX-2, SERPINE2, COL1A1, and COL3A1 were assessed immunohistochemically. The serum IL-6 and IL-10 levels were determined by the ELISA. IL6, IL10, and TNF mRNA expressions were assessed by qRTPCR. Results. The high levels of IL-6 in the serum of patients (p = 0.0159) and IL10 mRNA in BC tissue (p = 0.0316) were associated with an increase in the number of CD68+ TAMs. The pronounced infiltration of CD163+ TAMs correlated with an increase in the systemic level of IL-10 (p = 0.0357), IL-6 (p = 0.0286), and local TNF expression (p = 0.001). The increased SPP1 expression was accompanied by an increase in CD163+ TAMs (p = 0.008) against the background of a decrease in the CD68+ Mj population in BC tissue (p = 0.0271). The high levels of COX-2 were also directly correlated with the degree of M2-like Mj infiltration (p = 0.0357). At the same time, COL1A1 expression was associated with increased infiltration of both TAM phenotypes, while high COL3A1 expression was associated with a decrease in CD68+ Mj in tumor tissue. The bioinformatic analysis confirmed the obtained results and also allowed us to highlight the features of the tumor microenvironment composition, which depended on the degree of TAM infiltration in BC tissue of different molecular subtypes. Conclusions. The results demonstrated the existence of a single regulatory axis, “TAMs — cytokines — ECM”, which determined the development of the immunosuppressive and invasive BC microenvironment. The predominance of CD163+ Mj against the background of increased levels of IL-10, SPP1, and COX-2 was associated with a high degree of BC malignancy.